Troubling Water: Shale Energy and Waterscape Transformation in a North American Extraction Zone - Willow, Anna J. (Anthropologica, 2017)
As hydraulic fracturing to facilitate shale energy extraction expands into new regions, how people think about water’s multifaceted relationships to their lands and lives is being complicated and confounded. Drawing on in-depth interviews with 31 concerned residents of Ohio (United States), I argue that extraction “troubles” water in ways that extend far beyond empirical documentation of toxic contamination. My account illuminates how physical and conceptual relationships with water are concurrently and recursively transformed. For many Ohioans, formerly positive experiences of emplacement and embodiment are now infused with apprehension and alienation. As water infiltrates and motivates conversations about human health, residents’ rights, and contested knowledge, it has become culturally meaningful in newly anxiety-infused and hyper-vigilant ways. At the same time, water has come to fill a prominent political and oppositional position in unconventional extraction debates.